Visor - Razzi, Sahira Fakhrul; Wan Rosnan, Wan Nur Atira Nadirah; Othman, Siti Amira (Penerbit UTHM, 2020)
A visor is a piece of plastic object that can protect or cover the eyes area. Visor is designed transparent to protect the face and eyes. Therefore, the visors can disguise as a mask. For example, some of helmet in suit of the armour can protect our eyes and in automobile, the driver or front passenger can lower the part of windshield to block the sun. In the year 1924, Hathway has invented the car visor. Originally, he calls it as the glare shield because its function to block out the harmful sun’s x-ray. Therefore, Henry Ford from the creator of the Ford company patented the Hathway’s invention in 1938 that led many innovations to Ford Corp. The main of this purpose is to reduce the direct sunlight to driver’s eyes.